Strategies in Ballistics Reconstruction in Shooting Deaths: Checklist, Methods, Tricks, and Pitfalls (Global Journal of Medical Research, 2024)
Background The multidisciplinary type of Forensic Ballistics science is an essential database for the medical examiner to define the most compatible sequence of events and to motivate reconstructive hypotheses In gunshot victims analysis of biological data alone may be insufficient for recon-structive purposes Knowledge of the basic general principles relating to mechanisms indicators operating systems power supplies types of bullets and so on can make the difference between a sterile autopsy and one that can be useful to judicial investigations Results The reconstruction of the event the final phase of criminal investigation must include the interpretation and re-composition of the various elements of evidence and the overall evaluation of the same to obtain a legal characterization Therefore it can be very difficult to express a scientifically valid and sufficiently motivated opinion on important issues relating to the immediacy or otherwise of death the duration of survival the possibility of residue acts committed by the victim after the injury or autonomous movements or other acts conscious such as invocations for help recognition of persons report of lived events The less early the investigator s intervention at the crime scene the more difficult it will be to collect data and evidence correctly
Keywords: firearm; ballistic; medical examiner; forensic science